KAJIAN ETNOBOTANI TUMBUHAN OBAT ETNIS MELAYU DI DESA SUNGAI BARU DAN DESA SEMPADIAN KABUPATEN SAMBAS - dra, In; Husni, Harnani; Sisilia, Lolyta (JURNAL HUTAN LESTARI, 2014)
The purpose of this study was to determine the species of medicinal plants and how to use and processing by the Malay ethnic communities in the Sungai Baru village and Sempadian village Sambas Regency. The method used in the study were interviews that emic approach. The selection of respondents was done by using snowball sampling as many as 19 respondents. Results of interviews with people in the Sungai Baru village and Sempadian village Sambas Regency, earned as many as 73 species of medicinal plants and 41 families were used by the community. Of the 73 species of medicinal plants are 39 species (53.42%) were herbs, 49 species (67.12%) used are leaf, 41 species (56.16%) processing by means of ground, 41 species (56.16 %) the use of taped manner, 44 species (60.27%) are single herb types, 53 species (72.60%) to treat the disease, 37 species (50.68%) the result of cultivation and 66 species (90.41%) were the plants are easy to find. Keywords : Medicinal plants, Malay ethnic, Sambas Regency